2017
DOI: 10.1002/cncr.30894
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional view of racial differences in access to prostate cancer care

Abstract: Background Racial disparities in prostate cancer treatment and outcomes are widespread and poorly understood. We sought to determine whether access to care, measured across multiple dimensions, contributed to racial differences in prostate cancer. Methods The Philadelphia Area Prostate Cancer Access Study (P2 Access) included 2374 men diagnosed with localized prostate cancer in 2012–2014. Men were surveyed to assess their experiences accessing care (response rate 51.1%). We determined appointment availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
(38 reference statements)
0
17
0
Order By: Relevance
“… 25 Muralidhar et al (2017) Disparities in the Receipt of Local Treatment of Node-positive Prostate Cancer Population-based (NCDB) 9,771 Men with clinical N1M0 PCa diagnosed from 1998 to 2012 Black, lower income, older, and Medicaid beneficiary or no insurance patients are less likely to receive local treatment for node-positive PCa and are associated with reduced OS. 26 Pollack et al (2017) A multidimensional view of racial differences in access to prostate cancer care Survey-based 2,374 Men diagnosed with localized PCa between 2012 and 2014 Black men with PCa are younger and more likely to have Medicaid insurance, lower income, and a high school education or less. Black men report less availability to care and a lower level of perceived quality of care and doctor-patient communication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 Muralidhar et al (2017) Disparities in the Receipt of Local Treatment of Node-positive Prostate Cancer Population-based (NCDB) 9,771 Men with clinical N1M0 PCa diagnosed from 1998 to 2012 Black, lower income, older, and Medicaid beneficiary or no insurance patients are less likely to receive local treatment for node-positive PCa and are associated with reduced OS. 26 Pollack et al (2017) A multidimensional view of racial differences in access to prostate cancer care Survey-based 2,374 Men diagnosed with localized PCa between 2012 and 2014 Black men with PCa are younger and more likely to have Medicaid insurance, lower income, and a high school education or less. Black men report less availability to care and a lower level of perceived quality of care and doctor-patient communication.…”
Section: Discussionmentioning
confidence: 99%
“…Reports analyzing SES, an individual's relative societal position based on factors such as occupation, education, income, and disparities, generally concluded that lower SES is associated with a decreased likelihood of receiving RT for prostate cancer. 5 , 6 , 19 , 21 , 22 , 24 , 25 , 26 More specifically, lower income is paralleled to greater odds of not receiving dose-escalated or proton therapy. 24 However, patients with Medicare and Medicaid are more likely to receive proton therapy than those without or with private insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, only 5% of deaths are due to tumor-related factors. 5,25 Pollack et al found that poorer access was associated with worse perceived quality of care and physician-patient communication. 5,25 However, racial differences in treatment were found not mediated or modulated by access to care but by socioeconomic factors.…”
Section: Socioeconomic Disparities Among Black Communities and Prosta...mentioning
confidence: 99%
“…5,25 Pollack et al found that poorer access was associated with worse perceived quality of care and physician-patient communication. 5,25 However, racial differences in treatment were found not mediated or modulated by access to care but by socioeconomic factors. Black men have lower treatment availability than white men due to limited insurance coverage, travel longer distances to healthcare clinics, or have shortages of healthcare providers.…”
Section: Socioeconomic Disparities Among Black Communities and Prosta...mentioning
confidence: 99%